2017
DOI: 10.1002/2017jc012906
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations of ichthyoplankton assemblage in the northeastern South China Sea influenced by the Kuroshio intrusion

Abstract: The distribution and assemblage of ichthyoplankton related to local hydrographic features, especially intrusion of the Kuroshio Current (KC) and Guangdong Coastal Current (GCC) in the northeastern South China Sea (NESCS) were investigated in this study. A total of 193 species of ichthyoplankton belonging to 141 genera and 66 families were recognized in summer 2015 and late‐winter 2016. The ichthyoplankton assemblage was identified with distinct seasonal differences, and the differences were responded well with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Several studies have suggested that hydrological conditions, i.e., temperature, salinity and primary production were considered to significantly affect the occurrence and distribution patterns of ithchyoplankton (Hillgruber and Kloppmann, 1999;Franco-Gordo et al, 2002;Aceves-Medina et al, 2004;Lee and Go, 2005;de Macedo-Soares et al, 2014;Huang et al, 2017). In the present study, the eggs of Trichiurus were associated with specific water masses.…”
Section: Spawning Ground Distributions and Hydrological Conditionsmentioning
confidence: 49%
“…Several studies have suggested that hydrological conditions, i.e., temperature, salinity and primary production were considered to significantly affect the occurrence and distribution patterns of ithchyoplankton (Hillgruber and Kloppmann, 1999;Franco-Gordo et al, 2002;Aceves-Medina et al, 2004;Lee and Go, 2005;de Macedo-Soares et al, 2014;Huang et al, 2017). In the present study, the eggs of Trichiurus were associated with specific water masses.…”
Section: Spawning Ground Distributions and Hydrological Conditionsmentioning
confidence: 49%
“…For the data analysis below and specific calculation above (e.g., IRI), we combined the number of egg and larva samples together (Zhang et al, 2016;Huang et al, 2017;Hou et al, 2021a). A short hatchery period (i.e., hours to several days) and limited independent swimming capability of larvae were also the considerations for the combination of egg and larva data for analyses (Woynarovich and Horváth, 1984;Pauly and Pullin, 1988;Lechner et al, 2016;Downie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The variance inflation factor (VIF) was conducted to examine the collinearity between independent environment variables. VIF < 10 indicated that the environmental variables were not collinear and were fit for CCA (Graham, 2003;Huang et al, 2017). The importance of the environmental variables was measured by interset correlation coefficients, when the value of interset correlation coefficients ≥| ±0.4| variables were regarded conservatively as biologically important (Rakocinski et al, 1996;Ramos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kurogi et al (2012) discerned that the Japanese conger spawns in the area along the Kyushu-Palau Ridge around 17°N, 136°E. In the western Pacific, ichthyoplankton research has focused on coastal waters due to the logistical and economic considerations of investigations (Huang et al, 2017;Zhang et al, 2019a;Zhang et al, 2020;Hou et al, 2021). Surveys carried out in the open ocean are generally focused on the Kuroshio Current region (Su et al, 2011;Sassa and Takasuka, 2019), the Oyashio Current region (Shida et al, 2007), and their transitional waters (Aoki and Miyashita, 2000;Sassa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%